Improvement Of Ergonomic Cassava Removal Device Design With REBA (Rapid Entire Body Assessment) Approach In Tanjung Harap Village, Serbajadi District - Satrio, Dimas; Suliawati, Suliawati; Hernawati, Tri (SEAN Institute, 2023)
The goal to be achieved in this study is to improve the cassava fruit plucking device that applies to the harvesting process so that it becomes an ergonomic auxiliary tool by considering the safety, comfort, effectiveness of workers in doing work. This type of research is included in correlational type descriptive research with the method used in the form of the REBA (Rapid Entire Body Assessment) method is one method to analyze and provide observations of work postures quickly and easily. From the results of the study, the REBA score was obtained from the sum of the total grub A score and the total Grub B score and activity value, the effectiveness value obtained was 1 and the REBA score obtained was 10 where the number indicated high discomfort so that workers expended a lot of energy when doing work which resulted in many complaints of pain felt by workers thus it was necessary to redesign the tools used to Pulling out cassava fruit so that it can reduce the discomfort of workers and reduce complaints felt by workers.